Legal Certainty on the Execution of a Fiduciary Whose Movable Object Has Been Transferred to Third Parties - Livia Kusumadiani Putri; Benny Djaja (PT Publikasiku Academic Solution, 2023)
The debtor does not have the legality or rights before the law to transfer the fiduciary guarantee object to a third party and the transfer of the fiduciary guarantee object without the approval of the creditor becomes invalid. This compensation is because the debtor has committed an unlawful act, therefore it requires innovation or renewal debt in this case the old debt is removed and replaced with a new debt in accordance with Chapter 1413 Civil Code. Fiduciary Guarantee Act Should provide more specific arrangements regarding the position of objects that have been made object fiduciary guarantee because things made object Collateral are the main key in terms of providing guarantees from debtors to creditors. Given the fact that there are still many of them constraint-obstacles faced by creditors during the execution process of fiduciary collateral objects.